Pemodelan UML (Unified Modeling Langueage) dalam Perancang Sistem Informasi Pembayaran Uang Komite di SMP 4 Mauliru Berbasis Website - Resni Ina Chintika; Yustina Rada; Hawu Yogia Pradana Uly (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Along with the advancement of time, technology in the era of globalization demands that humans work more professionally, and it is required in various fields or public institutions and organizations that use computers to support operational activities and internet networks across different levels of society. SMP Negeri 4 Mauliru is one of the Junior High Schools located in Mauliru Village, Kambera District, East Sumba Regency, East Nusa Tenggara Province. This school has a mission to improve the quality of education and always strives to provide quality guidance to its students. The payment of the Committee Fund is an agreement among the parents or guardians of students to support the school's needs that are not covered by the BOS (School Operational Assistance) funds. One of the school's operational activities that is essential for supporting the Committee Fund payment system still uses a conventional system, particularly in the preparation and payment of the committee fund, where a ledger book is still used for recording payments. This results in a long process and frequent errors in ledger book entries. The Committee Fund is a recurring payment that students must pay to the school once a month. The purpose of this research is to create a Web-Based Committee Fund Payment Information System at SMP Negeri 4 Mauliru to facilitate the school treasurer in recording committee fund payments in the ledger book. This research uses the waterfall development method. Waterfall is the most commonly used software development model. Several stages in the waterfall model include: Analysis, Design, Implementation, Testing, and Maintenance. Based on the results obtained, the average value of 70% falls within the